OP0093 THE INCIDENCE AND RISK FACTOR OF NEW CAROTID PLAQUES AND THE PROGRESSION RATE OF CAROTID PLAQUES IN PATIENTS WITH RHEUMATOID ARTHRITIS IN 6 YEARS PROSPECTIVE CASE CONTROL STUDY. -TOMORROW STUDY-. (June 2019) - Anno, Shohei; Inui, Kentaro; Okano, Tadashi; Mamoto, Kenji; Sugioka, Yuko; Tada, Masahiro; Koike, Tatsuya; Nakamura, Hiroaki
Abstract : Background: Cardiovascular disease is one of the complications of rheumatoid arthritis (RA). Patients with RA show higher rates of cardiovascular disease mortality and overall mortality compared with individuals without RA. The presence of an abnormally increased intima–media thickness (IMT) in the carotid artery and carotid plaques on carotid ultrasound are useful for assessing the presence of subclinical atherosclerosis. A greater presence of carotid artery IMT and carotid plaques is a predictor of cardiovascular disease events. Objectives: The objective of this study was to evaluate progression of carotid plaques in 6 years by comparing 2011 and 2017, and to assess the risk factors of progression. Methods: This study included 208 patients with RA and 204 age- and sex-matched controls (Co) in the TOtal Management Of Risk factors in Rheumatoid arthritis patients to lOWer morbidity and mortality (TOMORROW) study. This was a 10-year cohort study that started in 2010. Carotid ultrasound was performed in 2011 and 2017. Ultrasound examination of bilateral carotid arteries was performed using high-resolution B-mode ultrasound (HI VISION Avius; Hitachi Aloka Medical, Tokyo, Japan) with a 6- to 18-MHz liner array transducer. IMT was evaluated as the distance between the luminal–intimal interface and the medial–adventitial interface. IMT was measured using two calipers on the frozen frame of a suitable longitudinal image. The upper limit of normal for IMT was defined as 1.0 mm. Lesions with any focal structure that protruded into the vessel lumen for at least an IMT ≥ 1.1 mm were defined as atherosclerotic plaques. Subsequently, the plaque score was assessed as the sum of the maximal thicknesses of all plaques in bilateral carotid arteries in the scanning area. Plaque scores were categorized as follows: none, no plaques; mild, score of 1.1–5.0; moderate, score of 5.1–10.0; and severe, score of > 10.0. Results: A total of 175 patients with RA (mean age: 58.9 ± 12.7 years, female ratio: 85.7%, mean disease duration: 15.0 ± 11.7 years) and 185 Co (mean age: 58.5 ± 12.5 years, female ratio: 84.3%) were finally analyzed. Carotid plaques were observed more frequently in the RA group than in the Co group in 2011 (n = 82 vs n = 66, p = 0.04). However, the incidence of new plaques was not significantly different between the RA and Co groups (n = 33 vs n = 44, p = 0.94). Age (p = 0.015) and the presence of diabetes (p = 0.009) were higher in patients with RA and new plaques than in those without new plaques. Multivariate logistic regression analysis did not show that RA was a risk factor for the incidence of new plaques (OR: 0.90, 95% CI: 0.47–1.73, p = 0.750). However, the presence of hypertension (OR: 3.11, 95% CI: 1.43–6.74, p = 0.004), the presence of diabetes (OR: 6.13, 95% CI: 1.13–33.4, p = 0.036) were risk factors for the incidence of new plaques. The plaque score became advanced in the RA and Co groups (both p < 0.001) in 6 years. Conclusion: There are no significant differences in the incidence of new plaques and the progression rate of the plaque score between patients with RA and Co. This finding might due to the recent advances in RA treatment, such as methotrexate or biologic DMARDs. In patients with RA, the presence of hypertension and diabetes represents a risk factor for the incidence of new plaques. Acknowledgement: We wish to thank Atsuko Kamiyama, Tomoko Nakatsuka and the members of the Osaka City University hospital clinical research center. Disclosure of Interests: Shohei Anno: None declared, Kentaro Inui Speakers bureau: Takeda Pharmaceutical, Pfizer Japan, Daiichi-Sankyo Co.Ltd., Abbvie, Mitsubishi Tanabe Pharma Corporation, Janssen Pharmaceutical, Chugai Pharmaceutical, Ono Pharmaceutical, Eisai Co.Ltd., Eli-Lilly, Nippon Kayaku Co., Ltd., Maruho Co., Ltd, Kaken Pharmaceutical Co., Ltd., Tadashi Okano Speakers bureau: AbbVie, Kenji Mamoto: None declared, Yuko Sugioka: None declared, Masahiro Tada Speakers bureau: Abbvie, Astellas Pharma, Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Janssen Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Ono Pharmaceutical, Pfizer Japan, Takeda Pharmaceutical, Tatsuya Koike Speakers bureau: AbbVie, Astellas Pharma Inc., Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Janssen, Lilly, Mitsubishi Tanabe Pharma Corporation, MSD, Ono Pharmaceutical, Pfizer, Roche, Takeda Pharmaceutical, Teijin Pharma, and UCB, Hiroaki Nakamura: None declared